Teacher leadership: Are Jamaican schools ready to embrace the concept? [PowerPoint presentation] - Davies, Rose (My University, 2013)
The concept of teacher leadership is not entirely new, having its early roots in John Dewey's philosophy of democratic and progressive education. In this approach, the classroom teacher is regarded as a critical contributor to the overall progress and success of the school. In recent years, the concept of teacher leadership has experienced a resurgence in the United States of America (USA), associated with a general dissatisfaction within the education sector about the unsatisfactory outcomes of school improvement and reform projects, both at home and internationally (Danielson, 2006; Murphy, 2005). The critics of school reform failure argue that the demands of 21st century education require less of the leadership approaches in which all power, authority, and responsibility to successfully improve schools reside in the principal as leader. Schools need "all hands on deck" in a new paradigm of leadership that encourages more shared and distributed leadership that meaningfully engages the classroom teacher. The call for increased teacher leadership comes from the recognition that "without teachers' full participation and leadership any move to reform education, no matter how well intentioned, is doomed to failure" (Lieberman and Miller, 1999). The School of Education at UWI, Mona, introduced a new master's degree programme in Teacher Education and Development into its offerings in the 2010 academic year. A new course, "Teacher Leadership," was included among the core courses of the programme. A key feature of the Teacher Leadership course is the main assessment task, which requires students to design and execute a mini project aimed at some element of school improvement, while assuming the role of teacher leader, and to document the experience within the interpretive framework of the literature on teacher leadership. This paper shares experiences from two cohorts of course participants as they executed their school improvement projects within their various school contexts. The author analyses the experiences and draws inferential conclusions relative to the question, "Are Jamaican schools ready to embrace the concept of teacher leadership?"
Paper presented at the Biennial Conference of The University of the West Indies Schools of Education, 23-25 April, 2013, St. Augustine, Trinidad and Tobago
Keywords: Teacher leadership; School administration; Educational leadership; Student teachers; Masters degrees; Teacher education; Postgraduate students; Project evaluation; Conference papers; Jamaica